2020
DOI: 10.1039/d0ob00303d
|View full text |Cite
|
Sign up to set email alerts
|

Acid–base-sensitive allylic oxidation of 2-allylbenzoic acids to form phthalides

Abstract: Allylic oxidation of 2-allylbenzoic acids to phthalides, instead of Wacker-type isocoumarins, was achieved with 1,2-bis(phenylsulfinyl)ethane palladium(ii) acetate (White catalyst) and oxygen in DMSO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…In 2020, Hou et al reported an allylic oxidation of 2allylbenzoic acids in presence of White catalyst (Scheme 17). [22] Nine examples of 3-ethylidenephthalides were obtained with average to good yields as a mixture of Z and E stereoisomers.…”
Section: Miscellaneous Cyclizationsmentioning
confidence: 99%
“…In 2020, Hou et al reported an allylic oxidation of 2allylbenzoic acids in presence of White catalyst (Scheme 17). [22] Nine examples of 3-ethylidenephthalides were obtained with average to good yields as a mixture of Z and E stereoisomers.…”
Section: Miscellaneous Cyclizationsmentioning
confidence: 99%
“…The enantioselective synthesis of 3-vinyl phthalides and butenolides is of interest due to their potential as synthons [13] towards an array of bioactive compounds. [4] To initiate the study, we selected 1 a for catalyst screening (Scheme 2). Initial trials focused on the use of Au-and Pd-complexes with P,P-, N,N-, and P,N-ligands and AgOTf as a halide scavenger.…”
mentioning
confidence: 99%
“…The enantioselective synthesis of 3-vinyl phthalides and butenolides is of interest due to their potential as synthons [13] towards an array of bioactive compounds. [4] To initiate the study, we selected 1 a for catalyst screening (Scheme 2). Initial trials focused on the use of Au-and Pd-complexes with P,P-, N,N-, and P,N-ligands and AgOTf as a halide scavenger.…”
mentioning
confidence: 99%
“…Considering that esters and lactones are ubiquitous in biologically active compounds, [4] preparation by AAA would also be extremely useful, but this is problematic because they are easily ionized under the conditions and are therefore prone to racemization. [5] Trost notes that the problem is "more severe than it appears at first glance" [5a] and con-sequently ester-forming Pd-AAA is scarce.…”
mentioning
confidence: 99%